Characterization of focal liver lesions: Use of mangafodipir trisodium (MnDPDP)-enhanced MR images - Aydın KARABACAKOĞLU,; Yüksel ADIGÜZEL,; Serdar KARAKÖSE,; Ertuğrul KAYAÇETİN,; Rahime HAYKIR, (Turkish Journal of Gastroenterology, 2019)
-